Technological innovation and the distribution of employment growth: A firm-level analysis - Flavio Calvino (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
This work studies the firm-level relationship between different types of innovative activities and employment growth rates. Improving on previous investigations on the topic, it combines a dynamic panel analysis of the effects of different types of product and process innovation on employment growth with an outlook on the whole conditional employment growth distribution. Results show that product innovation - especially in terms of good new to the entire market - has a positive effect on employment growth. This role is likely to be particularly relevant for both fast-growing and shrinking firms. Process innovation appears instead to have less clear-cut dynamics, consistently with existing evidence. Among different types of process innovation, the introduction of novel auxiliary processes appears to be more positively linked with employment growth.
Keywords: O30; L25; L60; C23; C21; J23; 330; Innovation; Employment growth; Dynamic panel methods; Quantile regression